2013
DOI: 10.1161/atvbaha.113.301765
|View full text |Cite
|
Sign up to set email alerts
|

Histone and DNA Methylation–Mediated Epigenetic Downregulation of Endothelial Kruppel-Like Factor 2 by Low-Density Lipoprotein Cholesterol

Abstract: Objective-Low-density lipoprotein (LDL) cholesterol induces endothelial dysfunction and is a major modifiable risk factor for coronary heart disease. Endothelial Kruppel-like Factor 2 (KLF2) is a transcription factor that is vital to endotheliumdependent vascular homeostasis. The purpose of this study is to determine whether and how LDL affects endothelial KLF2 expression. Approach and Results-LDL downregulates KLF2 expression and promoter activity in endothelial cells. LDL-induced decrease in KLF2 parallels c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
67
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(76 citation statements)
references
References 39 publications
3
67
0
1
Order By: Relevance
“…But, soon it was realized that modern genomic technologies like SNP array, gene expression microarray and microRNA array were not sufficient to explain the genetic inclination in patients with CAD. Thus, GWAS showed that only 10.6% of people with atherosclerosis had a probable heritable genetic factor [10,11]. In the remaining cases epigenetic studies identified specific CAD risk loci with the DNA methylation status to play significant role [10,11].…”
Section: Complex Cardiac Atherosclerotic Disorder: Genomewide Associamentioning
confidence: 99%
“…But, soon it was realized that modern genomic technologies like SNP array, gene expression microarray and microRNA array were not sufficient to explain the genetic inclination in patients with CAD. Thus, GWAS showed that only 10.6% of people with atherosclerosis had a probable heritable genetic factor [10,11]. In the remaining cases epigenetic studies identified specific CAD risk loci with the DNA methylation status to play significant role [10,11].…”
Section: Complex Cardiac Atherosclerotic Disorder: Genomewide Associamentioning
confidence: 99%
“…Both histone-and DNA-methylases were implicated in the LDL-induced repression of KLF2 transcription in endothelial cells. LDL-induced endothelial dysfunction effects were prevented by pharmacological inhibition or gene silencing of DNMT [258]. DNA methylation was also implicated in the reduced autophagy of THP-1 macrophages upon exposure to oxidized LDL (oxLDL) [259].…”
Section: Histone Deacetylasesmentioning
confidence: 99%
“…Interestingly, a recent report showed that KLF2 is downregulated by LDL, and that the repression of KLF2 is mediated by both DNA and histone methylation, 8 suggesting that the oxLDL-induced repression of KLF2 is not solely mediated by miR-92a, but that other epigenetic phenomena also play an important role. Both endothelial KLF2 and KLF4 have been shown to be atheroprotective.…”
Section: Article See P 434mentioning
confidence: 99%
“…4 Inhibition of miR-92a also reduced the expression of the active form of nuclear factor-κB, phospho-p65, an important driver of inflammation, and promoted the expression of NOS3, 4 both targets of KLF2 and KLF4. 7 Interestingly, a recent report showed that KLF2 is downregulated by LDL, and that the repression of KLF2 is mediated by both DNA and histone methylation, 8 suggesting that the oxLDL-induced repression of KLF2 is not solely mediated by miR-92a, but that other epigenetic phenomena also play an important role. Both endothelial KLF2 and KLF4 have been shown to be atheroprotective.…”
mentioning
confidence: 99%